Low incidence of deep venous thrombosis after laparoscopic cholecystectomy - (:unkn) unknown (Springer-Verlag, 1995)
The effects of the increased intraabdominal pressure that occurs during laparoscopic cholecystectomy and the effects of the reverse Trendelenburg position adopted for the procedure on deep venous thrombosis (DVT) were investigated prospectively. Thirty patients who underwent laparoscopic and 13 who underwent open cholecystectomy for symptomatic cholelithiasis were investigated for postoperative DVT. Lower extremity venous blood flow was examined by color Doppler ultrasonography before and after operations. Thrombus formation was not found in the femoral, popliteal, or iliac veins of any of the patients who underwent either open or laparoscopic cholecystectomy. None of the patients in either group displayed signs of DVT or pulmonary embolus. We concluded that the incidence of DVT does not increase with laparoscopic cholecystectomy. © 1995 Springer-Verlag.
Keywords: deep venous thrombosis; Doppler ultrasonography; laparoscopic cholecystectomy